The coordinated interaction or regulation between floral pigments and volatile organic compounds - Yueqing Li; Tingting Bao; Jia Zhang; Hongjie Li; Xiaotong Shan; Huijun Yan; Shadrack Kimani; Liangsheng Zhang; Xiang Gao (Horticultural Plant Journal)
Floral color and scent are crucial for plant–environment interactions, especially in reproduction by attracting pollinators for fertilization. They also have wide applications in cosmetic, pharmaceutical, and nutraceutical industries. Plant pigments are typically classified as chlorophylls, flavonoids, carotenoids, and betalains, while volatile organic compounds (VOCs) are grouped as terpenes, phenylpropanoids/benzenoids, and fatty acid derivatives. Significant progresses have been made in understanding the biosynthesis and regulation of these floral pigments and VOCs. Despite differences in their biosynthetic pathways, floral pigments and VOCs are biochemically connected and exhibit synergistic interactions during flower development and in response to biotic and abiotic stresses, suggesting the existence of pleiotropic regulators or complex mechanisms co-regulating their biosynthesis. In this review, we summarize and outline the metabolite pathways mainly integrating flavonoids, carotenoids, terpenes, and phenylpropanoids/benzenoids. We also provide a series of scenarios illustrating the coordinated regulation of floral color and scent. Finally, we suggest areas for future research. We hope this review will spark interest in this research direction and stimulate further studies.